A comparative study of terrestrial gamma dose rate in air measured by thermoluminescent dosimeter, portable survey meter and HPGe gamma spectrometer. (November 2016) - Huang, Yan-Jun; Guo, Gui-Yin; He, Yi; Yang, Li-Tao; Shan, Zhen; Chen, Chao-Feng; Shang-Guan, Zhi-Hong
Abstract: In this paper, three different widely-used measurement techniques for environmental gamma dose rate were studied and compared, i.e., the thermoluminescent dosimeter, the portable survey meter and the spectrometric analysis. Thirteen investigation sites were selected, and the TLDs were arranged to accumulate the radiation signals during an interval of about one quarter, the instant dose rates by using a portable survey meter were collected around the site, and top surface soils were sampled in the surroundings for radionuclides analyzing in laboratory. The results from these methods were compared, which revealed high correlations. The differences and possible uncertainties for the three methods were analyzed, inspired a further study should be conducted to have more successful estimation of dose rate in surface air. Highlights: Gamma dose rate was measured around a proposed nuclear power plant in siting stage. Three measurement methods for dose rate were used by TLDs, portable survey meter and spectrometric analysis. Correlations between the values from different methods were analyzed. The differences and the uncertainties of the dose rate from the different methods were analyzed.